Risk factors for nonunion following tibiotalocalcaneal arthrodesis: A systematic review and meta-analysis. Issue 1 (January 2022) - Patel, Sumit; Baker, Lauren; Perez, Jose; Vulcano, Ettore; Kaplan, Jonathan; Aiyer, Amiethab
Highlights: First meta-analysis to identify potential risk factors for nonunion following tibiotalocalcaneal arthrodesis. Performed using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and methodology registered with the International prospective register of systematic reviews (PROSPERO). Prior neuropathic conditions have strong evidence for failure to achieve union. Studies in our review suggest that diabetes mellitus can lead to failure of fusion. Abstract: Background: The goal of this study is to review the literature to identify risk factors for nonunion after tibiotalocalcaneal arthrodesis (TTCA) and stratify them based on strength of evidence. Methods: Five databases were searched from inception to May 17th, 2020. Abstracts and full-text articles were screened for those that included risk factors predictive of nonunion following TTCA. Results: Eight studies involving 624 patients were included and 33 potential risk factors for nonunion were identified. Strong evidence supported prior peripheral neuropathic conditions as risk factors for nonunion following surgery (OR: 2.86, 95% CI: 1.56–5.23). Conclusion: TTCA is an effective salvage procedure but is associated with high nonunion rates. The results of our meta-analysis suggest that prior peripheral neuropathic conditions have strong evidence for failure to achieve union. Surgeons should be cognizant of these risks when performing TTCA and carefully monitor patients with the aforementioned comorbidity to achieve successful results.